(3GdfLhe GdTGQbGJ aj GdUfGFY GdeMJGL EdjgG aj Yde GdejbGJs - (3eMeO GdOeTbj , eMeO Hf CHj GdNjQ GdMSfj GdOeTbj, bWH GdOjf,J (B700 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3Efi GSJNQJ Gddg JYGdi ai hVY ahGFO egeGJ dGHO efgG def CQGO GdJhUd Edi af GdhVYjGJ s
(3BNQgG (B:s
(3hEf TFJ Cda Ydjg hfLGQG YQGbjG hGcJH Hg cGdRhQO hGddg GYde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B293s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B357 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B102 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3UfGYg (B28) s
Keywords: (3Gdadcs